The ‘owl of misfortune’ or the ‘phoenix of prosperity’? Re-thinking the impact of the Mongols - Daniel C. Waugh (Journal of Eurasian Studies, 2017)
The impact of Mongol conquests across Eurasia is still controversial: did they destroy everything in their path or rather create a “Mongol peace” under which the Silk Road exchanges flourished? Too often medieval authors are cited merely for their negative reaction to the Mongols. Yet both the written sources and evidence from archeology show a picture of some complexity that requires critical analysis. The emphasis here is on archeology, often ignored or slighted by historians of the Mongols, and on evidence from Central Asia and Eastern Europe, primarily as reported in Russian-language scholarship. The impact of the Mongols varied depending on the location and the priorities of the new conquerors.